Radiotherapy for recurrent prostate cancer: 2018 Recommendations of the Australian and New Zealand Radiation Oncology Genito-Urinary group. Issue 2 (November 2018) - Lieng, Hester; Hayden, Amy J.; Christie, David R.H.; Davis, Brian J.; Eade, Thomas N.; Emmett, Louise; Holt, Tanya; Hruby, George; Pryor, David; Shakespeare, Thomas P.; Sidhom, Mark; Skala, Marketa; et al.
Abstract: The management of patients with biochemical, local, nodal, or oligometastatic relapsed prostate cancer has become more challenging and controversial. Novel imaging modalities designed to detect recurrence are increasingly used, particularly PSMA-PET scans in Australia, New Zealand and some European countries. Imaging techniques such as MRI and PET scans using other prostate cancer-specific tracers are also being utilised across the world. The optimal timing for commencing salvage treatment, and the role of local and/or systemic therapies remains controversial. Through surveys of the membership, the Australian and New Zealand Faculty of Radiation Oncology Genito-Urinary Group (FROGG) identified wide variation in the management of recurrent prostate cancer. Following a workshop conducted in April 2017, the FROGG management committee reviewed the literature and developed a set of recommendations based on available evidence and expert opinion, for the appropriate investigation and management of recurrent prostate cancer. These recommendations cover the role and timing of post-prostatectomy radiotherapy, the management of regional nodal metastases and oligometastases, as well as the management of local prostate recurrence after definitive radiotherapy.